Martha's Vineyard Basketball: How a Resort League Defied Notions of Race and Class - Bayne, Bijan C. (Rowman & Littlefield Publishers, 2015)
Year round on Martha’s Vineyard Island off Cape Cod, Massachusetts, residents and vacationers have played basketball—almost since the game was invented. The Oak Bluffs summer league on the Island was innovative, ethnically diverse, welcomed female players, and fostered thousands of friendships. President Obama, NBA All-Star Kyrie Irving, and Family Matters sitcom star Jaleel White have all played basketball on Martha’s Vineyard, as did future college stars, authors, war heroes, and entrepreneurs. Their stories touch current events from World War I through the Civil Rights Movement—and even include the filming of the blockbuster Jaws. Martha’s Vineyard Basketball: How a Resort League Defied Notions of Race and Class follows the rich history of basketball on the Island and tells the stories of the players and coaches themselves. During the heyday of Martha’s Vineyard basketball in the 1970s and ‘80s, the courts provided a place for friendships that looked past social class and race—a unique situation given that nearby cities such as Boston were sites of violent demonstrations against integration. Original interviews with those who were there not only reveal the racial dynamics on Martha’s Vineyard, but also relate amusing anecdotes of encounters with celebrities that include Charles Lindbergh, James Cagney, Frank Sinatra, and future star James Taylor. Martha’s Vineyard Basketball reveals little-known aspects of the Island, shares the realities and triumphs of residents and vacationers alike, and demonstrates the unifying power of basketball. New Englanders, basketball fans, and those interested in race and class relations will all find this book a noteworthy account of a singular place.